Diversidade de espécies zooplanctônicas e a heterogeneidade de recursos em diferentes ambientes de uma planície Neotropical. - Fernandes, Ana Paula Capelari (2013)
The species diversity is a topic in community ecology that has been widely discussed, and the factors which influence it have generated much interest and have been the focus of several studies. Among these factors, there is the resource heterogeneity, and its increase is crucial for the coexistence of a larger number of species, which would result in greater diversity. It was investigated the relationship between the "heterogeneous resources and the species diversity" to explain the diversity of zooplankton species in a neotropical floodplain environment. It was assumed a linear relationship between the zooplankton diversity and the richness and diversity of the species, equitability of the algal communities and resources size, and a unimodal relationship between the zooplankton diversity and the abundance of the periphyton and planktonic algal. These attributes of algal communities were considered as heterogeneous resource aspects. Samples were taken of the coastal and pelagic plankton of different environments of the floodplain of the upper Paraná River, in November 2011. Our results showed that the heterogeneity of the food resources influenced the diversity of the zooplankton species and its different groups. The equitability of the algal communities was an important predictor of the relationship investigated. The zooplankton diversity in the coastal region was more related to algal periphyton community than to phytoplankton, suggesting that there is a compartmentalization of zooplankton in lowland environments, despite the constant changes in the water body between the two regions and, as a result, the fauna. The absence of linear relationships between the zooplankton diversity and the phytoplankton algal heterogeneity in the pelagic region suggest that other factors may be influencing this relationship, such as predation, since this region does not provide places of refuge, and other sources of food resources, as planktonic protozoa and bacteria. Thus, further studies are necessary to clarify these relationships between zooplankton diversity and resource heterogeneity, mainly concerning other factors such as predation and microbial food chain.